Characterization of Nanoemulsion Prepared from Self-emulsifying Rifampicin and its Antibacterial Effect on Staphylococcus aureus and Stap. epidermidis Isolated from Acne (Dhaka University Journal of Pharmaceutical Sciences, 2016)
In this study, three different self emulsifying drug delivery systems of rifampicin (SEDD-R) were made using oleic acid and different surfactants such as Tween 80, Chremophor RH 40 and Chremophor EL designated as RN-TW, RN-CRH and RN- CEL. These self-emulsifying systems were converted to rifampicin nanoemulsion by adding water under sonication. The resulting particle sizes were found to be 192.7 nm, 183.4 nm and 179.2 nm for RN- CEL, RN-CRH and RN-TW, respectively using Zetasizer. Drug content, entrapment efficiency, in vitro drug release and pH stability tests was performed. Drug content and entrapment efficiency for RNTW, RN-CRH and RN- CEL were found as 0.9945% & 0.9835%, 0.9720% & 84.31% and 74.58 % & 56.89%, respectively. The release of drug from RN-TW, RN-CRH and RN-CEL occurred for 450-, 330- and 240- minutes, respectively. The pH stability study demonstrated that all formulations retained maximum drug at pH 5.8. Antibacterial effect of the preparations was evaluated against S. epidermidis and S. aureus isolated from acne and showed effective results.Dhaka Univ. J. Pharm. Sci. 14(2): 171-177, 2015 (December)